Short communication. Behavioural activities of two dairy cow genotypes (Holstein-Friesian vs. Jersey x Holstein-Friesian) in two milk production systems (grazing vs. confinement) - Roca-Fernández, A. I.; Ferris, C. P.; González-Rodríguez, A. (Spanish Journal of Agricultural Research, 2013)
The aim of this work was to study the behavioural activities of two cow genotypes, Holstein-Friesian (HF) vs. Jersey × Holstein-Friesian (Jx), when managed within two production systems, a low inputs grazing (G) system vs. a high inputs confinement (C) system. Eighty spring calving cows (HF, n=40 and Jx, n=40), from AFBI Hillsborough (Northern Ireland) experimental dairy cattle, were randomly assigned to one of two production systems (G, n=40 and C, n=40) in a block design with a 2×2 factorial arrangement of four treatments (HF-G, HF-C, Jx-G and Jx-C). Cow behavioural activities (feeding, lying, standing and ruminating) were registered on three periods at 20-min intervals, between 16.00-22.00 h and 07.00-14.00 h. Average milk yields (kg cow-1 day-1) were higher (p<0.001) in the C system (27.0) than in the G system (20.1), with differences (p<0.001) between the two cow genotypes (HF, 25.1 vs. Jx, 22.0 kg cow-1 day-1). Milk production system showed an effect on cow behavioural activities. Animals on the G system spent more time (p<0.001) grazing (522 min) than those on the C system spent feeding (173 min). Cows on the C system spent more time (p<0.001) lying (C, 411 vs. G, 212 min), standing (C, 236 vs. G, 85 min) and ruminating (C, 244 vs. G, 141 min) than those on the G system. There were differences between periods for time spent lying (p<0.001), feeding (p<0.05) and ruminating (p<0.001), while time spent standing did not differ between periods. Cow genotype had no effect on any of the behavioural activities.